Hyperprogression after anti-programmed cell death ligand-1 therapy in a patient with recurrent metastatic urothelial bladder carcinoma following first-line cisplatin-based chemotherapy: a case report - Mao S; Zhang J; Guo Y; Zhang Z; Wu Y; Zhang W; Wang L; Jiang Geng; Yan Y; Yao X (Dove Medical Press, 2019)
Shiyu Mao,1,* Junfeng Zhang,1,* Yadong Guo,1,* Ziwei Zhang,1 Yuan Wu,2 Wentao Zhang,2 Longsheng Wang,1 Jiang Geng,1 Yang Yan,1 Xudong Yao1 1Department of Urology, Shanghai Tenth People’s Hospital, Tongji University, Shanghai 200072, PR China; 2Department of Urology, Shanghai Tenth People’s Hospital, Anhui Medical University, Hefei 230032, PR China *These authors contributed equally to this work Background: Immune checkpoint blockade targeting programmed cell death ligand-1 (PD-L1)/programmed death-1 (PD-1) signaling was approved recently for locally advanced and metastatic urothelial bladder carcinoma (UBC). Some patients experience a very rapid tumor progression, rather than clinical benefit, from anti-PD-L1/PD-1 therapy.Case presentation: A 58-year-old male diagnosed with non-muscle-invasive bladder cancer 3 years ago received transurethral resection of bladder tumor (TURBT) and intravesical chemotherapy. TURBT was repeated a year later for recurrent and progressive UBC. Following further disease progression, he received a radical cystectomy (RC), pathologically staged as T2bN2M0, and adjuvant cisplatin-containing combination chemotherapy. When his disease progressed to metastatic UBC, he was started on anti-PD-L1 monotherapy and experienced ultrarapid disease progression within 2 months; imaging scans ruled out pseudoprogression. We observed a fourfold increase in tumor growth rate, defined as the ratio of post- to pretreatment rates. Next-generation sequencing of formalin-fixed paraffin-embedded RC tissues showed MDM2 amplification without MDM4 amplification, EGFR aberrations, or DNMT3A alterations. Immunohistochemistry showed grade 2+ PD-L1 labeling intensity of the RC tissues, with 15%–25% and 5%–10% PD-LI immunopositive tumor cells and tumor-infiltrating immune cells, respectively.Conclusion: Even in cases with PD-L1-positive tumors, MDM2 gene amplification may result in failure of anti-PD-L1 immunotherapy and rapid tumor growth. Therefore, genomic profiling may identify patients at risk for hyperprogression before immunotherapy. Keywords: urothelial bladder carcinoma, programmed cell death ligand-1, immune checkpoint blockade, hyperprogression, MDM2